Characteristics of Quality Requirements for LPG Rubber Hose and LPG Thermoplastic Elastomer Hose in Indonesia - Mulyono, Ary Budi; Purwanto, Endi Hari (Proceeding International Conference on Religion, Science and Education, 2022)
One of the causes of LPG gas cylinder explosion cases in Indonesia is the leakage of LPG gas hoses. LPG hoses are susceptible to corrosiveness to hydrocarbons and ozone. Standards or technical specifications of a product can guarantee product quality and improve product safety. This study aims to identify the characteristics of quality requirements of LPG rubber hose and LPG thermoplastic elastomer hose related to resistance to n-pentane (hydrocarbon) and ozone compounds (parameter in Indonesian National Standard (SNI). This study used a qualitative descriptive method based on primary data (test results) and secondary data (literature study). Sampling test using purposive sampling. This study concluded that there were differences in characteristics of LPG hose quality requirements for resistance to n-pentane and ozone.